Effects of an acute respiratory disease challenge on growth, thermal radiation, and acute phase protein production in growing pigs - J A Loughmiller; M F Spire; B W Fenwick; S Hogge; J Walker; R D Stott; A Moser; Jim L Nelssen; Michael D Tokach; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1999)
Forty-seven growing pigs (initially 65 ± 2 lb) were used in a metabolism study to determine the effects of a single respiratory disease challenge on growth performance, infrared thermal radiation, and serum acute phase proteins. Thirty pigs were challenged with Actinobacillus pleuropneumonia, and seven pigs were assigned to an ad libitum-fed nonchallenged control group. Ten additional nonchallenged pigs were pair-fed the feed intake of an A. pleuropneumonia-challenged counterpart. There were five 4 d collection periods (d 4 to 7, d 8 to 11, d 12 to 15, d 16 to 19, and d 22 to 25), and the A. pleuropneumonia challenge occurred on d 8. Serum haptoglobin and amyloid A concentrations increased in the disease-challenged pigs compared to pigs in both nonchallenged treatments. Growth performance was decreased during the immune challenge period but partially recovered by the end of the experiment on d 25. Average surface body temperature also decreased briefly in the disease-challenged pigs compared to pigs in both nonchallenged treatments. These results suggest that a single acute respiratory disease challenge is accompanied by long-term compromises in growth performance, but perfonnance partially recovers as the pigs overcome the immunological challenge.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Growing pigs; Growth; Acute phase proteins; Respiratory disease